Data mining and data visualization for analysing the rate of bed availability at hospitals due to COVID 19 - Thanuj Kumar S; Vinitha Dominic K; Sumathi V (Archive of Biomedical Science and Engineering - Peertechz Publications, 2021)
This study started in July 2020 during the COVID 19 pandemic period to analyze & visually illustrate insights of data of biomedical facilities' information. The objective of this study is to present major issues faced, solutions found, and a roadmap for future work in developing visual analytics for interactive & data visualization for biomedical facility applications. This chapter starts with a brief introduction of data mining and data visualization, followed by a description of data mining tasks and we'll build a decision tree model, followed with the concrete examples on various data visualization charts(namely Histogram, Bar Chart, Pie Chart, Line graph, etc), this paper which is intended for visual analysis of "Bed availability rate" in hospitals and decision support for patients and is based on Data Mining & Visualization techniques.